Customer concentration and stock liquidity - Do, Trung K.; Huang, Henry Hongren; Le, Anh-Tuan (Journal of Banking & Finance, 2023)
This research empirically examines how customer concentration affects stock market liquidity of supplier firms. We find that firms with a concentrated customer base are strongly and positively associated with stock market liquidity, which is robust to a battery of model specifications and endogeneity issues. The positive relationship between customer concentration and liquidity is concentrated among firms with relatively small size, high financial constraints, and high information asymmetry. Further analyses provide supportive evidence on the monitoring role of principal customers in improving firms’ stock liquidity. Overall, these findings suggest that relationships with principal customers serve as valuable signals for the underlying quality of firms, and thus firms in such relationships are able to achieve favorable economic outcomes.